Equilibrium and kinetic studies for the adsorption of arsenic from aqueous medium using Cyanex 301-impregnated natural and synthetic fibrous supports. (1st January 2012) - Gupta, Bina; Irfan, Zareena Begum
The direct decontamination of As(III), the more toxic species of arsenic has been developed in the present research work using the fibrous supports impregnated with the extractant Cyanex 301. Bis (2, 4, 4-trimethylpentyl) dithiophosphinic acid (Cyanex 301) was used as an extractant for impregnating the fibrous supports namely the natural oil catcher (OC) and the synthetic kapok fibre (KFO). Batch experiments were performed as a function of process parameters: sorption time, concentration of metal ion, impregnant, weight of impregnated fibrous supports and pH. Results showed that As(III) was adsorbed by Cyanex 301-impregnated fibrous supports over a wide pH range with the quantitative removal efficiency in few minutes. The uptake of arsenic obtained at natural water pH is promising. Equilibrium and kinetic studies of As(III) adsorption by both natural and synthetic fibres impregnated with Cyanex 301 was also investigated.